2014
DOI: 10.1016/j.rgmxen.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Total serum calcium and corrected calcium as severity predictors in acute pancreatitis

Abstract: Objectives: To evaluate total serum calcium (TC) and albumin-corrected calcium (ACC) as prognostic severity factors in acute pancreatitis (AP). Methods: Ninety-six patients were included in the study. They were diagnosed with AP and admitted to the Hospital Regional de Veracruz within the time frame of January 2010 to December 2012. AP severity was determined through the updated Atlanta Classification (2013). TC and ACC values were measured in the first 24 hours of admittance and the percentages of sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Low serum ionized calcium (Ca 2+ ) levels have been demonstrated as playing an important role in detecting patients with severe AP [159]. Gutiérrez-Jiménez et al [160] verified a sensitivity, specificity, positive predictive value, and negative predictive value of 67%, 82%, 27%, and 96% at a maximum cut-off of 7.5 mg/dL for total calcium in predicting severe AP. Yu et al [161] showed that low serum Ca 2+ is an independent risk factor affecting the severity of AP.…”
Section: Total Calciummentioning
confidence: 99%
“…Low serum ionized calcium (Ca 2+ ) levels have been demonstrated as playing an important role in detecting patients with severe AP [159]. Gutiérrez-Jiménez et al [160] verified a sensitivity, specificity, positive predictive value, and negative predictive value of 67%, 82%, 27%, and 96% at a maximum cut-off of 7.5 mg/dL for total calcium in predicting severe AP. Yu et al [161] showed that low serum Ca 2+ is an independent risk factor affecting the severity of AP.…”
Section: Total Calciummentioning
confidence: 99%
“…Although, Maher M. et.al found in a study performed on 149 patients that total calcium level has a P value of 0.67 and is statistically insignificant as a predictor of severity(7), but Gutierrez-Jimenez A. A. et al found that total calcium is a powerful predictor of severity in the first 24 hours (8). There are differences in the population numbers between the two studies and this may explain the varying results.…”
Section: Discussionmentioning
confidence: 98%
“…Body mass Index (BMI), hematocrit value, blood glucose level and pleural effusion detected by plain chest radiograph are simple tests and promising predictors to the severity of AP and provide significant data for clinical decision making and proper management (7). However, some other predictors like total serum calcium level showed mixed results (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Albumin corrected calcium (mg/dl) = total calcium (mg/dl) + 0.8 × [4-serum albumin (g/dl)]. 7 The modified CT severity index (CTSI) or Balthazar score was determined at admission and 48 hours at some time and any point of time during admission as per the need of the patient. 8 Ethical clearance was obtained from the institution review board.…”
Section: Methodsmentioning
confidence: 99%